The role of social distance in the relationship between police-community engagement and police coercion - McCarthy, Molly (Policing and society, 2021)
While there is a considerable body of evidence on the influence of individual and situational, and to a lesser extent community factors, on police use of force, little is known about the influence of police agency factors on use of force by police. Greater use of community policing approaches has recently been recommended for U.S. policing agencies, in the wake of a series of high-profile police-involved deaths of predominantly African American citizens. However, there is limited empirical evidence that community policing can influence or impact the use of force by police. The current study uses an online survey of Australian police officers to examine whether frequency of community engagement affects officers’ attitudes towards coercive and non-coercive policing responses to a vignette, and whether social distance might explain this relationship. Regression analyses demonstrated that community engagement was positively related to endorsement of non-coercive policing responses and negatively related to endorsement of coercive policing responses. Social distance mediated the former relationship, but not the latter. These results suggest that community policing approaches may increase the propensity for non-coercive policing responses, and that a reduction in social distance to the community is one pathway through which this occurs.